Use of liposomal bisphosphonates to deplete macrophages for cancer immunotherapy - Hafeman, Scott D., author; Dow, Steven, advisor; Gustafson, Daniel, committee member; Thamm, Douglas, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2011)
In order for continued growth, metastasis and evasion from immune surveillance, tumor cells are dependent on a complex matrix of supportive cells and tissues. These cells make up a significant percentage of the tumor mass and contribute to the hallmarks of malignancy. Of these, the tumor associated macrophage (TAM) has perhaps the most diverse role. In the majority of tumor types studied, increased percentages of these cells in the tumor correspond to a poorer prognosis for the patient. Macrophages are critical in wound healing, and as such provide a wide variety of factors that may be co-opted by the tumor to support its continued growth and metastasis. Macrophages are capable of producing a wide variety of growth factors that directly promote tumor cell growth. These factors can also be used to induce tumor cell migration and invasion, which are critical steps in metastasis. They also produce matrix metalloproteinases that actively degrade basement membranes, further aiding in invasion and metastasis. Macrophages also produce many factors that help induce angiogenesis, providing vital blood supply to the developing tumor. Through both direct and indirect mechanisms they are vital to providing new tumor blood vessels. In addition to these direct tumor aiding effects, macrophages also play a critical role aiding in both local and global immunosuppresion in tumor patients, which allows the established tumor to continue to evade the immune system. Therefore, the targeting and killing of TAMs could potentially be a promising new adjunct to traditional cancer therapies, and may increase the efficacy of traditional therapeutics. One potential drug for this purpose is liposomal clodronate. This drug is produced by encapsulating the bisphosphonate drug clodronate in a liposome. As a free drug, clodronate is very effective at inducing apoptosis of osteoclasts, a close relative to the macrophage. Encapsulation in a lipid bilayer prevents the dissemination of the drug to the bone matrix and instead allows for systemic distribution. However, only cells that phagocytize and degrade the lipsome are susceptible to killing by the enclosed clodronate. Liposomal clodronate has been used extensively to deplete macrophages in studies of autoimmune disease and more recently in tumor models. However the systemic depletion of tumor associated macrophages using liposomal clodronate (LC) has not been previously evaluated in clinical trials, and the effects of systemic LC administration on tumor growth have not been fully elucidated. Studies presented here sought to further determine the role of tumor associated macrophages in tumor growth by studying the effects of their depletion. Specifically, in vitro studies were used to determine an optimal formulation of liposome to more effectively deliver the bisphosphonate drug to macrophages. Using multiple murine macrophage cell lines and proliferation assays the most effective depleting liposome was determined. This formulation consisted of a net neutral charged phosphatidylcholine head group combined with an incorporated mannose group. These liposomes were then evaluated in vivo for their ability to deplete macrophages systemically. Once again, the modified liposome formulation was most effective. The drug was then evaluated for its ability to decrease tumor growth in a mouse fibrosarcoma model, using MCA 205 tumors subcutaneously implanted into C57BL/6 mice. The drug's ability to deplete tumor associated macrophages was also evaluated. Tumor growth rates and tumor associated macrophage numbers were significantly decreased in mice treated with liposomal clodronate as compared to untreated mice or those treated with liposomal PBS. Additional studies were undertaken to determine if liposomal clodronate could be used as an effective cancer therapeutic in a spontaneous tumor model. The tumor evaluated was malignant histiocytosis (MH). This tumor was chosen as it is a tumor derived from macrophages or dendritic cells, and LC could potentially have both primary anti-tumor effects as well as efficacy due to depletion of TAMs. In vitro studies were undertaken which showed that LC was capable of effectively killing MH cells. Based on these results, a clinical trial was conducted for dogs with MH. Dogs were treated with 0.5 mL/kg of liposomal clodronate IV every other week for six treatments. A total of 12 dogs were treated in the study. Treated dogs were evaluated for tumor response, changes in circulating blood cells, and changes in circulating cytokines. We were able to observe a 40% biologic response rate (BRR). The development of a fever was positively correlated with response. Responding dogs also had an increase in neutrophils and a decrease in monocytes while non-responding dogs did not. A significant reduction in serum Il-8 levels occurred post LC treatment. As the clinical availability of LC is currently limited to experimental use additional studies were conducted to determine if combining free bisposphonates, which are readily available, with traditional chemotherapeutics could cause synergistic killing of MH cells in vitro. The combination of clodronate with vincristine or zoledronate with doxorubicin demonstrated synergistic killing in vitro. Further evaluation of these combinations will be necessary to determine if they have a similar effect in vivo.
Keywords: cancer; canine; immunology; macrophage; malignant histiocytosis; tumor